Legal Challenges in the Development of Ecotourism as Part of the Tourism Business - Purnama, Yulian; Sofian, Achmad Gilang; Rusmini, Andin (PT. LITERASI SAINS NUSANTARA, 2023)
Ecotourism is a crucial segment in the rapidly growing tourism industry. Despite being considered a sustainable solution, uncontrolled development can have negative impacts on the environment. This research aims to analyze the legal challenges in the development of ecotourism as part of the tourism business. The study employed a comprehensive literature review utilizing qualitative analysis to gain a thorough understanding of the topic spanning from 1972 to 2023. The findings indicate that the development of ecotourism as part of the tourism business faces several legal challenges. The Tourism Law Number 10 of 2009 serves as the primary foundation, but its implementation in ecotourism raises issues such as the misalignment of business interests and environmental preservation, insufficient participation of local communities, and suboptimal natural resource management. The sustainability of ecotourism requires synergy between the development of tourism business and environmental preservation. There is a need for enhanced regulatory implementation by strengthening community participation in decision-making and increasing their understanding of the economic and environmental benefits of ecotourism.